Perlindungan Hukum Pidana Penggelapan Debitur Atas Harta Kekayaannya(Boedel Pailit) Yang Mengakibatkan Kerugian Terhadap Kreditur - Muhammad Dirgantara Indonesia (Jurnal JURISTIC, 2026)
The purpose of this study is to identify and analyze the criminal law protection of debtors embezzlement of their assets (Boedel Bankruptcy) which results in losses to creditors. With the formulation of the problem What is the legal position of the debtor's embezzlement of his assets that causes creditor losses?, What are the legal barriers to the debtor embezzlement of his assets that result in losses to creditors?, The approach method in this study is the normative juridical method. the debtor's assets that cause losses to creditors, after being sentenced to bankruptcy, is a criminal act of embezzlement as regulated in Article 372 of the Criminal Code and Article 400 paragraph (1) of the Criminal Code because the fulfillment of the criminal elements is fulfilled, the bankrupt debtor is uncooperative in carrying out the legal process due to lack of the level of legal awareness of the bankrupt debtor.